Using Tourism Brochure to Improve Students’ Writing Ability in Report Text: an Experimental of the Elevent Grade Students of SMAN I Godong-Purwodadi in Academic Year 2016/2017 - Siti Nurlaela; Mohammad Wahyu Widiyanto (ETERNAL (English Teaching Journal), 2016)
The objectives of the study are: (1) to find out is the students’ ability to writing report text taught using tourism brochure, (2) to find out is the students’ to writing report text taught using picture, and (3) to find out whether or not there is a significant different of writing report text between the students who are taught using tourism brochure and taught using picture. This study used true experimental design. The writer used experimental class and control class. The subject of the study was the eleventh grade students of SMA N 1 Godong-Purwodadi. There were 5 classes with 200 students. The writer chose XI mipa 3 with 40 students as the experimental class and XI mipa 4 with 40 students as the control class. The result of the study shows that the students’ ability in learning process has significant difference between Tourism Brochure and Picture as media. It could be seen the average score of post-test between experimental class was 78,6 and control class was 68,3. In other hand, the t-test formula shows that t-test is higher than t-table, where 8,91> 2,021 (on a level significance 5%). It means that the improvement in post-test of experimental class was higher than control class. The used Tourism Brochure as media in enhancing students’ ability in studying English writing report tex. Therefore, the positive hypothesis (Ha) is accepted, and the negative hypothesis (Ho) is rejected. From the results, the writer concludes that the use of Tourism Brochure as a media significantly enhance students writing report text. Moreover, the writer suggests to teachers to use Tourism Brochure as a media to make easy and help students in writing report text and explore their ides, so that they are motivated to study English.